The adverse mental health of carers: Does the patient diagnosis play a role? - Loi, S.; Dow, B.; Moore, K.; Hill, Keith; Russell, M.; Cyarto, E.; Malta, S.; Ames, D.; Lautenschlager, N. (Elsevier Ireland Ltd, 2015)
Objectives: The adverse mental health effects of caring have been studied, frequently in carers of people with dementia. Less is known about the mental health of carers of people with other conditions. This study compared depression and burden in older carers looking after people with a variety of conditions. Design, methods and measures: Over 200 older carers interested in participating in the Improving Mood through Physical Activity in Carers and Care-recipient Trial were included in this cross-sectional study, using the Geriatric Depression Scale (GDS) and Zarit Burden Inventory (ZBI). Results: Overall there were 43% of carers who were depressed and a quarter of them reported moderate-to-severe burden. Carers of people with physical conditions had the highest levels of depression and burden. Patient diagnosis, hours spent caring, and burden were associated with depression, while hours spent caring and carer depression were associated with burden. These factors contributed approximately 25-30% of the variance of depression and burden, respectively. Conclusions: The diagnosis of the patient was a factor associated with depression, and older carers of people with physical conditions were at the highest risk. It is important for clinicians to assess the mental health of all carers, regardless of the patient diagnosis.